Model Pemberdayaan Masyarakat Berbasis Potensi Lokal: Studi Program Kampung Kreatif Karisma Pertamina (K3P) - Arifin, Muhson; Trianingrum, Suci; Dewi, Primatika Pramana; Perkasa, Agil Bagus Putra (Journal of Administration, Governance, and Political Issues, 2024)
This research aims to analyze the community empowerment model based on local potential through the Kampung Kreatif Karisma Pertamina (K3P) program in Karangrena Village, focusing on the empowerment process, contributing factors, and the program's impact on the community. Using a qualitative approach, the study explores how K3P optimizes local resources to improve social, economic, environmental, and cultural aspects. The findings reveal that the program significantly empowers marginalized groups, including the elderly and women farmers, through cultural arts and agricultural activities. Environmentally, the program reduced erosion through reforestation and transformed livestock waste into organic fertilizer. Economically, participants experienced more than a 50% increase in income, while culturally, the community engaged in regular arts training sessions facilitated by the program. The success of K3P is attributed to human resources, infrastructure, social and economic support, and natural resources, all of which play a vital role in achieving the program’s goals. The diverse activities within the K3P program, framed as educational tourism in culture and agriculture, have not only improved local livelihoods but also attracted significant public attention.